ISSUES AND CHALLENGES IN LOCAL GOVERNMENT PROJECT MONITORING AND EVALUATION IN NIGERIA:THE WAY FORWARD - Igbokwe-Ibeto, Chinyeaka Justine (European Scientific Journal, ESJ, 2012)
Project monitoring and evaluation are important components of local government councils’ functions. Given the need to take governance to the grassroots, projects are regularly executed by this level of government. However, empirical evidences show that most local government councils incur huge financial losses and alienation of the citizenry due to poor project monitoring and evaluation to ascertain their level of compliance with laid down procedures of project management. The paper argues that given the catalogue of challenges facing project monitoring and evaluation in Nigerian local governments,unless some urgent and categorical steps are taken such as: adherence to due process in all facets of project planning and management involving the people of the grassroots in project initiation, formulation and execution, insistence on continuity on government projects irrespective of change of government or its personnel, availability of visionary and missionary leadership among other steps, government at the grassroots will continue to struggle to make any useful impact on the people’s life.